The Study on the Optimum Conditions of Concentrated Sulfuric Acid Hydrolysis of Rice Straws for Producing Reducing Sugar for Ethanol Fermentation - ศิวราศักดิ์ ผ่องศรี (Frontiers in Engineering Innovation Research, 2006)
The simplex method was applied to find the optimum conditions of concentrated sulfuric acid hydrolysis of rice straws for producing reducing sugar in this study. This method was conducted by using specified ratio of rice straws to 98% (w/w) sulfuric acid of 1:30 (g : mL) as constant parameter and variable parameters were weight of sulfuric acid. Hydrolysis time and temperature. It was found that the optimum conditions were required 63 rng sulfuric acid and used hydrolysis time for 37 minutes at 147 degree Celsius which maximum total reducing sugar obtained of about 8% (w/w). However simplex method was further applied to find weight of sulfuric acid required and hydrolysis time at constant temperature of 147 degree Celsius. It was found that the optimum conditions were double increased required sulfuric acid weight and hydrolysis time and also double total reducing sugar obtained of about 16 % by weight. This reducing sugar was fermented with 15% by volume Saccharomyces ccrevisiue RIT 02 for 40 hours to produce ethanol. Obtained ethanol from fermentation was 2.5 % by weight.